The Elongation of Biceps Muscle Tendon Unit After Rerouting of the Long Head of Biceps Tendon as Superior Capsular Augmentation: A Quantitative Measurement - Hailong Zhang, M.D., Ph.D; Chunyan Jiang, M.D., Ph.D (Elsevier, 2020)
Purpose: The purpose of this study was to investigate the elongation of the biceps muscle tendon unit after rerouting of the long head of the biceps tendon without transection, with and without release of the transverse humeral ligament in a 3-dimensional model. Methods: A total of 60 sets of computed tomography images of shoulders were acquired, and a point-cloud model was generated after 3-dimensional reconstruction. Simulation of rerouting of the long head of the biceps tendon was performed by assuming that the long head of the biceps tendon travels to the center of the greater tuberosity from the supraglenoid tubercle and then back to the bicipital groove distally, with or without the release of the transverse humeral ligament. The elongation of the biceps muscle tendon unit by both manners was measured and correlated with age, height, weight, body mass index, gender, and hand dominance. Results: The mean length of the long head of the biceps tendon is 74.22 ± 3.06 mm, and the length is significantly longer, at 112.23 ± 4.92 mm (P = 0.0002) and 96.47 ± 2.58 mm (P = 0.0004). The absolute elongation of the biceps muscle tendon unit after rerouting of the long head of the biceps tendon, without or with transverse humeral ligament release, showed significant differences, which were 38.73 ± 3.03 mm and 22.28 ± 3.25 mm, respectively (P = 0.0008). No significant correlations were observed between the amount of the elongation and the subject's age, height, weight, or body mass index. No significant difference was observed in the amount of the elongation between differing gender and hand dominance. Conclusions: Rerouting of the long head of the biceps tendon resulted in significant elongation of the biceps muscle tendon unit. Release of the transverse humeral ligament partially decreased this elongation. Clinical Relevance: Rerouting of the long head of the biceps tendon may lead to overtension of the biceps. If it is adopted in clinical use, transverse humeral ligament release is recommended.